Inovasi Pembelajaran Interaktif Mengenal Jenis Sampah untuk Anak Sekolah Dasar Dengan Media Game - Aditya Putra Ramdani; Nova Christina Sari; Diaz Aditya; Karima Elsami; Naimatul Husna; Achmad Solichan; Edy Winarno; Muhammad Zainudin Al Amin; Basirudin Ansor (Jurnal Pengabdian Masyarakat Waradin, 2025)
The issue of waste management remains one of the significant environmental challenges in Indonesia, mainly due to the lack of awareness and understanding from an early age. This article discusses the implementation of a community service program through innovative interactive learning using educational games "Reresik" and "Bersihkan Sampah di Laut" designed to enhance elementary school students' interest and understanding of waste management. The implementation method includes teacher training, the introduction of waste material, the application of educational games, and the evaluation of program effectiveness through satisfaction surveys. The results indicate that game-based learning methods significantly increase student enthusiasm, simplify understanding, and foster positive habits in maintaining environmental cleanliness. Moreover, the training provided to teachers improved their ability to integrate educational technology into the learning process. This program is expected to serve as a sustainable innovative learning model to raise environmental awareness among younger generations.